THE INFLUENCE OF SOCIAL MEDIA MARKETING ON MIE ENDESS PURCHASE DECISIONS THROUGH BRAND TRUST AS A MEDIATOR AMONG GENERATION Z CONSUMERS IN BANGKALAN REGENCY - Abimayu, Prawira; Dermawan, Rizky (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study is motivated by the increasing use of social media among Generation Z as the main source of product information, which significantly influences purchasing behavior, particularly in the food and beverage sector. As a micro, small, and medium enterprise (MSME), Mie Endess in Bangkalan Regency has implemented Social Media Marketing (SMM); however, its effectiveness is highly dependent on the level of Brand Trust established. This study formulates the problem of whether Social Media Marketing directly influences Purchase Decision and whether Brand Trust mediates this relationship. This study aims to analyze the effect of Social Media Marketing on Purchase Decision with Brand Trust as a mediating variable among Generation Z consumers of Mie Endess. A quantitative method was applied using purposive sampling, involving 120 respondents who had purchased Mie Endess and actively used social media. Data were collected through online questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 3.0 software. These findings highlight the importance of strengthening ethical digital marketing and trust-based strategies to enhance consumer confidence and purchasing decisions in MSMEs.